2013
DOI: 10.1292/jvms.12-0310
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Commercially Available Diabetic Prescription Diets on Short-Term Postprandial Serum Glucose, Insulin, Triglyceride and Free Fatty Acid Concentrations of Obese Cats

Abstract: ABSTRACT. Diet therapy is an important treatment component available for obese cats. In this study, the impact of four commercially available prescription diet regimens (1 for general use and 3 aimed at treating obesity and diabetes mellitus (DM)) on short-term postprandial serum glucose, insulin, triglyceride and nonesterified fatty acid (NEFA) concentrations was investigated with five obese cats. The diet regimens used were as follows: C/D dry (general use: moderate protein, moderate fat, high carbohydrate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…However, a similar response has previously been reported in healthy lean and obese cats after ingestion of some commercially available diets and was associated with a high increase in insulin. 17,18 Overall, the amplitude of the shifts in plasma glucose concentration was mostly slight and unlikely to be of clinical relevance (Tables 3 and 4). However, postprandial response may notably be affected by gender, 15 carbohydrate content of the diet, 19 carbohydrate source 20 and feeding management.…”
Section: Discussionmentioning
confidence: 99%
“…However, a similar response has previously been reported in healthy lean and obese cats after ingestion of some commercially available diets and was associated with a high increase in insulin. 17,18 Overall, the amplitude of the shifts in plasma glucose concentration was mostly slight and unlikely to be of clinical relevance (Tables 3 and 4). However, postprandial response may notably be affected by gender, 15 carbohydrate content of the diet, 19 carbohydrate source 20 and feeding management.…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting reports of the influence of diet on triglyceride concentrations in cats. Several studies have reported that a high-protein and low-carbohydrate diet does not significantly affect triglyceride concentrations in cats, 19,23,24 whereas others have shown that a high-fat diet results in a significant increase in triglyceride concentrations. 17,25,26 The current study showed that a high-protein diet increased triglyceride concentrations in healthy cats.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have reported that a high-protein and low-carbohydrate diet does not significantly affect serum triglyceride concentrations in cats. 19,23,24 In comparison, cats fed diets high in fat had significant increases in triglyceride concentrations. 17,25,26 Although high-fibre foods lower triglyceride concentrations in diabetic cats 20 they increase cholesterol concentrations in healthy cats.…”
Section: Introductionmentioning
confidence: 98%
“…viscous solutions and impairment of the digestive processes and the absorption of fat and glucose, slowing down the increase in blood sugar [Mimura et al 2013].…”
Section: Dietary Fiber Fractionsmentioning
confidence: 99%